Can genetically based clines in plant defence explain greater herbivory at higher latitudes? - Daniel Anstett; Jeffrey Ahern; Julia Glinos; N. Nawar; Juha-Pekka Salminen; Marc T. Johnson. (John Wiley & Sons, 2025)
Greater plant defence is predicted to evolve at lower latitudes in response to increased herbivore pressure. However, recent studies question the generality of this pattern. In this study, we tested for genetically based latitudinal clines in resistance to herbivores and underlying defence traits of Oenothera biennis. We grew plants from 137 populations from across the entire native range of O. biennis. Populations from lower latitudes showed greater resistance to multiple specialist and generalist herbivores. These patterns were associated with an increase in total phenolics at lower latitudes. A significant proportion of the phenolics were driven by the concentrations of two major ellagitannins, which exhibited opposing latitudinal clines. Our analyses suggest that these findings are unlikely to be explained by local adaptation of herbivore populations or genetic variation in phenology. Rather greater herbivory at high latitudes can be explained by latitudinal clines in the evolution of plant defences.